VD_FINDINFO HC / 2011 / 546 vom 8. November 2011 - VD Tribunal cantonal (2011)
RÉSILIATION, PROLONGATION DU BAIL À LOYER, ANNULABILITÉ | 271 al. 1 CO, 271 CO, 271a al. 1 let. a CO, 272 al. 1 CO, 272 al. 2 CO, 272 CO